Effects of iron addition on electrical properties and aging behavior of barium titanate ceramics - Jirapa Tangsritrakul (2018)
In this study, the influences of Fe addition on phase formation and electrical properties of Ba(Ti1 - xFex)O3 with x = 0 to 0.02 were investigated. In addition, aging behavior of the ceramics was also investigated. The XRD analysis showed that the crystal structure of Ba(Ti1 - xFex)O3 changed from tetragonal to hexagonal as Fe concentration increased to x = 0.015, causing a noticeable decrease in the dielectric properties. From ferroelectric hysteresis (P-E) loops measurements, with increasing Fe content the saturation polarization decreased, while the coercive electric field increased at low concentration (x ≤ 0.01) with tetragonal structure. At x ≥ 0.015, with paraelectric hexagonal phase, no P-E hysteresis loop was observed at room temperature. Room temperature aging study showed that the ferroelectric P-E hysteresis loops became constricted loops during aging in Ba(Ti1 - xFex)O3 with ferroelectric tetragonal phase. The dielectric constant also decreased during aging. Copyright © Taylor & Francis Group, LLC.